Top management support and electronic medical records effectiveness: A case study at Amanda Hospital - Widyasasmita, Mutiara Nurtika; Ricki, Agustinus Very (Institute of Computer Science (IOCS), 2025)
The adoption of Electronic Medical Records (EMRs) has significantly enhanced healthcare efficiency, accuracy, and data accessibility. However, successful EMR implementation is highly dependent on top management support. This study examined the role of leadership in facilitating EMR effectiveness at Amanda Hospital, Indonesia. A quantitative descriptive approach was employed with a cross-sectional design, involving 55 respondents comprising administrative staff, IT personnel, and healthcare professionals. Data were collected through structured surveys, interviews, and observations. The results indicated a strong positive correlation between top management support and EMR effectiveness. Leadership commitment played a crucial role in resource allocation, policy enforcement, and staff training, all of which contributed to successful EMR adoption. System usability and training availability were identified as key moderating factors, influencing user adaptation. Despite improvements in data accuracy, infrastructure limitations and system downtimes emerged as critical challenges. The findings emphasize the need for continuous managerial involvement, structured training programs, and robust IT infrastructure to sustain EMR effectiveness. This study provides valuable insights for healthcare institutions aiming to optimize EMR implementation by integrating technical, managerial, and policy-driven strategies.